Pay Few Subjects but Pay Them Well: Cost-Effectiveness of Random Incentive Systems - Christoph March; Anthony Ziegelmeyer; Ben Greiner; René Cyranek (Center for Economic Studies and ifo Institute (CESifo), 2016)
Most large-scale economic experiments use a between-subjects random incentive system-BRIS-which selects a subset of the participants at random and offers real payment only to the selected participants. We evaluate the relative impact of nominal payoffs and the selection probability on the incentive effectiveness of BRIS. High nominal payoffs and a tiny but unknown selection probability induce the monetary incentives in a large-scale Internet treatment. Two laboratory treatments complement the Internet treatment, one with high nominal payoffs and a moderate selection probability and the other with moderate nominal payoffs and a high selection probability. For the majority of our participants nominal payoffs have a bigger impact on the incentive effectiveness of BRIS than the probability of payment and the latter hardly dilutes the effects of monetary incentives. Our results suggest that cost-effective BRIS consist of high nominal payoffs and a small selection probability.
Keywords: C91; C93; D12; D81; 330; cost-effectiveness; random incentive system; large-scale experiments; risk aversion; decision error